The Influence of Work Ethics, Organizational Culture and Motivation on The Performance of Employees from The Office of Community and Village Empowerment of Central Kalimantan Province - Hansly; Rita Yuanita Toendan; Peridawaty (International Journal of Contemporary Sciences (IJCS), 2024)
Research in the field of management regarding the importance of human resources in improving performance. Work ethics are very much needed as is the implementation of organizational culture. This study used a sample size of 35 people as a measure for quantitative analysis using the SPSS application. The results show that work ethics, organizational culture and motivation are significant in improving performance, so that the goals of the organization are very good. This 79.1% result can be used as input for leadership and as an implication for being more open in informing about work ethics and work culture, which can then encourage employee motivation to improve performance. Future research could consider transformational leadership styles